Desimination of Technology Assistance for the Development of Road Network Geospatial Information in Murtigading Village, Bantul - Noor Mahmudah; Nursetiawan; Wahyu Nur Avian; Ikhwan Fachrurazi; Amri Rosyadi (Peneliti Teknologi Teknik Indonesia, 2021)
To realize sustainable village development, the village government is obliged to prepare the Village Medium-Term Development Plan (RPJM). Considering that the RPJM of Murtigading Village, Sanden District, Bantul Regency is still in the form of ordinary digital data, mapping and making maps of geospatial information for earth-oriented village infrastructure is very important in supporting integrated development planning and in accordance with the One Map Policy. This service activity aims to assist the Village Administration in mapping and developing thematic geospatial information (IGT) for roads and public infrastructure in Murtigading Village using the Quantum GIS (QGIS) version 3.10.1 program. The data used is a map of Indonesia's Earth and Quickbird imagery of Bantul Regency. This activity involved Murtigading Village Pamong, 18 Padukuhan Heads, and KPMD, both in preliminary surveys, data collection and mapping, making IGT roads and other public infrastructure with QGIS, synchronization and dissemination of geospatial information data. The results of the activity are in the form of a Geographical Information System (GIS)-based IGT map containing data on the distribution of locations, names, history, current network conditions, geometrics, and road pavements as well as public facilities in shape file (shp) format as well as thematic analog maps with a scale of 1:2000, 1:3000, 1:3,500, 1:4000, and 1:7000 which are expected to be guidelines in planning and prioritizing the development of village infrastructure that is right on target.